2013
DOI: 10.2991/itmr.2013.3.4.1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Critical Factors for Communicating With Customers on Social Networking Sites

Abstract: This paper undertakes a systematic review to gain insight into existing studies on the application of Social Network Sites (SNS). Our systematic review of studies from 1995 to 2012 examines the background and trend of research in the area and provides critical factors that organizations should consider for effectively use social networking sites to communicate with their customers. We note a huge growth in the number of academic papers on the topic since 1998. Seventeen factors were identified as a result of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In terms of teaching presence, it is recommended that the instructors pay adequate attention to contents that they choose for the Facebook page. Acknowledging the findings of Talaei Khoei and Talaei-Khoei [23], the student engagement occurs along the right amount of learning materials. Instructors should realize that the long-term engagement can only happen where there are many members of the group interacting.…”
Section: Figure 4 Value Of Facebook In Increasing the Students' Engagmentioning
confidence: 89%
See 1 more Smart Citation
“…In terms of teaching presence, it is recommended that the instructors pay adequate attention to contents that they choose for the Facebook page. Acknowledging the findings of Talaei Khoei and Talaei-Khoei [23], the student engagement occurs along the right amount of learning materials. Instructors should realize that the long-term engagement can only happen where there are many members of the group interacting.…”
Section: Figure 4 Value Of Facebook In Increasing the Students' Engagmentioning
confidence: 89%
“…There are two main reasons for that. First, Facebook has been proven as a successful platform in terms of user engagement [22], [23]. Second, students prefer Facebook for both socialize and facilitating peer learning.…”
Section: Introductionmentioning
confidence: 99%
“…This study has customized the guidelines for systematic reviews laid by Kitchenham (2004) and applied in several reviews [6] and conducted the review in four steps (as shown in …”
Section: Methodsmentioning
confidence: 99%
“…Public sentiments towards unfolding natural disasters are measured various ways by the social media platforms. For example, Facebook measures the level of public concern through 'likes' and 'dislikes' [6]. Since Twitter has extensively been used for posting opinions and situations, it has become the focus of sentiment analysis [25].…”
Section: E Digital Volunteerismmentioning
confidence: 99%
See 1 more Smart Citation